Analysis of Seed Vigor Using the Biospeckle Laser Technique - Roberto A. Braga; José Luís Contado; Karina Renostro Ducatti; Edvaldo A. Amaral da Silva (AgriEngineering, 2024)
Seed analysis is a cornerstone in advancing agriculture, with vigor tests playing a critical role in evaluating the physiological quality of seeds. However, monitoring seed vigor over time poses a significant challenge for the seed industry, as traditional methods are time-consuming and heavily reliant on subjective human judgment. Concerning these limitations, optical-based techniques have emerged as promising alternatives. Among them, the biological laser speckle phenomenon, rooted in optical interferometry, has proven effective in sensitively detecting and monitoring activity levels in living tissues. Known as the biospeckle laser (BSL) technique, this approach offers reliable results in assessing seed vigor. The BSL technique stands out due to its simplicity, rapid analysis, objectivity, and potential for automation, making it a valuable tool for seed analysis. This paper explores the state-of-the-art application of the BSL technique for evaluating seed vigor, highlighting successful approaches, identifying current challenges, and outlining areas for future research. It delves into the experimental setup for seed illumination and discusses the associated image processing methods. Furthermore, the paper examines the numerical and graphical outcomes, underscoring the BSL technique’s ability to carry out seed analysis by addressing the limitations of traditional methods and enhancing efficiency in the agricultural sector.